Biography Genre Variations: Iris Mudoch’s Life - Matiychak, Aliona (Pitannâ lìteraturoznavstva, 2015)
The article outlines historiography, epistemological and source study problems of Iris Murdoch’s biographies. Such types of biographies as academic and literary ones, memoirs, biographical essay and anti-biography are analysed. Individual techniques of biography writers are identified as well as the limits of authors’ interpretation and intermedial trends of the biographical genre are specified